2018
DOI: 10.1039/c8tc02726a
|View full text |Cite
|
Sign up to set email alerts
|

New red-emitting Schiff base chelates: promising dyes for sensing and imaging of temperature and oxygen via phosphorescence decay time

Abstract: New complexes of Zn(ii), Pd(ii) and Pt(ii) with Schiff bases are prepared in a one step reaction and show photophysical properties particularly interesting for applications in optical sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…And photostabilities of Ir(III) lms were measured in N 2 every 10 minutes. 51 The data in Fig. 10 indicated that emission intensities of Ir(III) lms were attenuated through continuous irradiation.…”
Section: Photostability Measurementsmentioning
confidence: 94%
“…And photostabilities of Ir(III) lms were measured in N 2 every 10 minutes. 51 The data in Fig. 10 indicated that emission intensities of Ir(III) lms were attenuated through continuous irradiation.…”
Section: Photostability Measurementsmentioning
confidence: 94%
“…9 The are many photochemically-induced biological processes associated with nitrogen-containing heterocyclic compounds, such as Schiff's bases. 10,11 These compounds have shown a broad spectrum of applications in pharmacology and medicine, 12 but they also serve as catalysts, 13 optical materials and dyes, 14,15 and play an important role in inorganic biochemistry. 16,17 Depending on their structure, compounds of this type have a wide range of biological activities and are well-known for their antibiotic activities, including anticancer, antiviral and anticonvulsant effects.…”
Section: Introductionmentioning
confidence: 99%
“…The QDs based chemosensors usually have QDs loaded on glass, because the Si-O tetrahedral structure in glass contributes to provide a stable environment for the formation of QDs. 135 Moreover, cadmium telluride (CdTe) QDs are widely used because CdTe crystals are more stable, particularly under high temperature, maintaining high crystalline purity (i.e., with minimal defects), thus providing high yield of fluorescence.. 136,137,138 Several turn-off fluorescent probes based on QDs for FA detection will be discussed as follows.…”
Section: Quantum Dots (Qds)mentioning
confidence: 99%